Granger causality analysis of the CEE stock markets including nonsynchronous trading effects - Olbrys, Joanna; Majewska, Elżbieta (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
This paper focuses on friction in trading processes in the context of the implications of nonsynchronous trading effects, especially in the CEE stock markets. We analyze the Granger causality, and we investigate both the whole sample May 2004 - April 2012 and two equal subsamples: the 'crisis' period and the 'post-crisis' period. Our results show several causal relationships in the whole sample period, in the case of the group of the biggest CEE stock market indexes and the group of the three Baltic market indexes. Moreover, to accommodate the 'nonsynchronous trading effect II' in the Granger causality tests, we propose a version of a VAR model with a modified dynamic structure of lags for the CEE and US stock market indexes. We observe a pronounced feedback relationship for almost all of the analyzed models, both in the whole sample period and in the two subsamples. In light of our results, it seems that taking into account the 'nonsynchronous trading effect II' plays a crucial role in examining the lead-lag relationships among the world stock markets
Argumenta Oeconomica, 2013, Nr 2 (31), s. 151-172
Keywords: CEE stock markets; market frictions; nonsynchronous trading; Granger causality; giełdy światowe; rynek akcji